Pengaruh Audit Internal Terhadap Kinerja Perusahaan Perbankan - Sri Rahayuningsih; Cornellius Nathanael Hartanto; Ratna Sefitriya; Herlina Manurung (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine and analyze the influence of internal audits on the performance of banking companies in Indonesia. Internal audit is an activity carried out to help a company achieve its goals. Good or continuously improving company performance can indicate good conditions within the company. This type of research is qualitative which will describe the influence of internal audit on company performance using the literature review method, where this method uses previous research articles as a data source and is used for the results and discussion. The results of this research, which are based on previous research, are that internal audits can have an influence on the financial performance of conventional banking companies with the number of internal audits carried out effectively by banking companies. Meanwhile, in sharia banking, internal audits have no effect on the company's performance.